2006
DOI: 10.1021/ol062577c
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 2,3-Dihydro-pyrrolopyridinones Using in Situ Generated Formimines

Abstract: A novel one-pot methodology is described for the synthesis of functionalized pyrrolopyridinones using in situ generated formimines and an ortho-lithiated pyridinecarboxamide species. Depending on the reaction conditions, this procedure allows versatile access to aminomethylated pyridinecarboxamides, 2,3-dihydro-pyrrolopyridinones, or 1,1-dialkylated 2,3-dihydro-pyrrolopyridinone derivatives. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ): δ = 3.63 (s, 2 H, 5‐H), 2.68 (tt, J H,H 1 = 10.2, J H,H 2 = 3.8 Hz, 1 H, 1‐H), 1.83–1.88 (m, 2 H, 2/2′‐H), 1.72–1.78 (m, 2 H, 3/3′‐H), 1.60–1.67 (m, 1 H, 4‐H), 1.25–1.36 (m, 2 H, 3/3′‐H), 1.14–1.23 (m, 1 H, 4‐H),1.04–1.14 (m, 2 H, 2/2′‐H) ppm. Spectroscopic data are in agreement with those reported in the literature . A solution of N ‐cyclohexyl‐aminoacetonitrile thus prepared (5.50 g, 39.8 mmol) in 35 mL of Et 2 O (abs.)…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…1 H NMR (400 MHz, CDCl 3 ): δ = 3.63 (s, 2 H, 5‐H), 2.68 (tt, J H,H 1 = 10.2, J H,H 2 = 3.8 Hz, 1 H, 1‐H), 1.83–1.88 (m, 2 H, 2/2′‐H), 1.72–1.78 (m, 2 H, 3/3′‐H), 1.60–1.67 (m, 1 H, 4‐H), 1.25–1.36 (m, 2 H, 3/3′‐H), 1.14–1.23 (m, 1 H, 4‐H),1.04–1.14 (m, 2 H, 2/2′‐H) ppm. Spectroscopic data are in agreement with those reported in the literature . A solution of N ‐cyclohexyl‐aminoacetonitrile thus prepared (5.50 g, 39.8 mmol) in 35 mL of Et 2 O (abs.)…”
Section: Methodssupporting
confidence: 87%
“…of ClCH 2 CN, 2.2 equiv. of K 2 CO 3 , MeCN, 20 h, reflux (79 %); B) 2.4 equiv. of amyl nitrite, Et 2 O, 20 h, room temp., then HCl(g), 1.5 h, room temp.…”
Section: Resultsmentioning
confidence: 99%
“…7 Nevertheless, the inclusion of a nitrogen atom in the aromatic ring could provide the opportunity to modulate both the pharmacodynamic and kinetic properties of pyrrolopyridines. 8 Several synthetically modified analogues of compound 1 have been prepared to evaluate their biological activity. 9 In connection with an ongoing project and with the goal of developing novel synthetic methodologies for gaining rapid access to new nitrogen heterocyclic compounds, we herein describe a rapid synthesis of a series of compounds 2 (Figure 1), which are aza-analogues of 1, based on an oxidative Ugi type reaction and the aza-Diels-Alder cycloaddition as post-condensation.…”
Section: Figure 1 Nuevamine and Its Aza-analoguementioning
confidence: 99%
“…[24][25][26][27][28] Previous studies in our laboratory confirmed that sulfomethylation is an efficient way to introduce the ASO 3 2 group into copolymers because it can give the copolymer remarkable antishearing ability, temperature resistance, and salt tolerance with simple operation and economic feasibility. 29,30 Hence, in this study, N,N-diallyl nicotinamide (DANA) was synthesized as described in the literature; 31,32 it was copolymerized with sodium acrylate (NaAA) and AM to obtain an AM/AA/ DANA copolymer. Furthermore, the ASO 3 2 group was used in AM/AA/DANA via sulfomethylation with the aim of improving the temperature tolerance and shear tolerance of the copolymer (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%